Psychological adverse effects of COVID-19 pandemic on health service providers: an online survey - Mohammad Hossein Somi; Ali Fakhari; Hosein Azizi; Habibeh Barzegar; Sanaz Norouzi; Vahab Aslrahimi; Mostafa Farahbakhsh (Middle East Current Psychiatry, 2022)
Abstract Background In the current situation of the COVID-19 pandemic, health service providers (HCPs) suffered from mental health consequences such as depression, anxiety, fear, and post-traumatic stress disorder (PTSD). The study aimed to evaluate the adverse psychological impacts of the COVID-19 pandemic on HSPs at the Tabriz University of Medical Science, North West of Iran. An online survey was conducted to assess the psychological adverse effects of COVID-19 during the pandemic of COVID-19 from May 2021 to February 2022. Psychological adverse effects including depression, anxiety, PTSD, and fear were measured using valid instruments. Overall, 298 HSPs responded to the questionnaires. Descriptive and multiple logistic regression analyses with crude and adjusted ORs were used to estimate mental health adverse effects. Results The overall prevalence of depressive symptoms, major depression disorder (MDD), anxiety, and probable PTSD were 58%, 9.1%, 61.7%, and 15%, respectively. The fear of COVID-19 scale (mean) was 17.6± 6.2. We found mental health adverse effects were higher in HSPs who worked in the treatment and health sections than HSPs in the support section. Having a history of mental disorder, HSP type (health and treatment), and female sex had a statistically significant association with MDD and depressive symptoms. Conclusions Mental health problems were high in HSPs. The study highlights the demand for support systems and appropriate interventions for improving HSPs’ mental health and well-being during the COVID-19 pandemic.